2023
DOI: 10.1071/rd23006
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves the ability of spermatozoa to bind with oocytes in the mouse

Abstract: Context and aims Melatonin is a powerful antioxidant regulating various biological functions, including alleviating male reproductive damage under pathological conditions. Here, we aim to analyse the effect of melatonin on normal male reproduction in mice. Methods Male mice received an intraperitoneal injection of melatonin (10 mg/kg body weight) for 35 consecutive days. The testis and epididymis morphology, and epididymal sperm parameters were examined. PCNA, HSPA2, SYCP3, ZO-1 and CYP11A1 expressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Adding melatonin in vitro can promote oocyte development in humans ( 14 ), mice ( 46 ), bovines ( 47 ), sheep ( 48 ), and swine ( 49 ). Our network meta-analysis results also showed that melatonin could promote goat oocyte development in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Adding melatonin in vitro can promote oocyte development in humans ( 14 ), mice ( 46 ), bovines ( 47 ), sheep ( 48 ), and swine ( 49 ). Our network meta-analysis results also showed that melatonin could promote goat oocyte development in vitro .…”
Section: Discussionmentioning
confidence: 99%